Variation in Repair of the Triangular Fibrocartilage Complex - Kootstra, Thomas J.M.; van Leeuwen, Wouter F.; Chen, Neal; Ring, David (Journal of Wrist Surgery, 2018)
Background There is controversy regarding the value of repair of the triangular fibrocartilage complex (TFCC). Given that an acute tear of the TFCC associated with a displaced distal radius fracture uncommonly benefits from repair, the role of repair in other settings is uncertain. Our impression is that TFCC repair is highly variable from surgeon-to-surgeon.Purpose The purpose of this study is to determine the rate of TFCC repair in patients who had a magnetic resonance imaging (MRI) scan of the wrist obtained for ulnar-sided wrist pain, and that showed signal changes in the TFCC. We tested the primary null hypothesis that there are no demographic or surgeon factors associated with repair of the TFCC.Patients and Methods Three hundred and ninety-four patients with ulnar-sided wrist pain and an MRI scan showing changes in the TFCC were included in this retrospective study. No patients had instability of the distal radioulnar joint (DRUJ) recorded in the medical record. Surgical repair of TFCC tears was used as the primary outcome during statistical analysis to identify factors associated with repair.Results Out of 394 (6%), 25 patients underwent TFCC repair. We found that 10% of the treating surgeons (4 out of 41) performed 80% of the procedures (20 out of 25). Patients who discerned a trauma prior to their symptoms and patients whose MRI showed signal changes primarily in the ulnar portion of the TFCC were more likely to have surgical repair.Conclusion We found that the rate of TFCC repair varies substantially from surgeon-to-surgeon. The observation that repair is more likely to happen when patients perceive themselves as injured suggests that perception of injury affects how patients and surgeons consider treatment options. To help avoid surgeries based on surgeon bias or patient misperception, we suggest studying the effect of tools that provide simple, balanced, dispassionate, and empowering information (e.g., decision aids) that can limit surgeon-to-surgeon variation.Level of Evidence Level IV.
Keywords: magnetic resonance imaging; repair; surgery; triangular fibrocartilage complex